Development of renewed waweguide system for microwave diagnostics in Uragan-2M stellarator - Pavlichenko, R.O.; Zamanov, M.V. (Problems of Atomic Science and Technology, 2022)
This paper presents initial proposal for the development of quasi-optical (QO) microwave technology for Electron Cyclotron Emission (ECE) and reflectometry diagnostics in the Uragan-2M (U-2M) stellarator. For the existed ECE radiometer systems and for the operational plasma parameters of U-2M new quasi-optical beam separation dichroic filter is designed. For such filter the mechanical parameters and performed attenuation characteristic are calculated. Frontend antenna/splitter system for the combined ECE/reflectometry radiation detection is presented. As an example, QO beam pattern for the ECE receiving antenna is numerically calculated.